PENGARUH STRATEGI DIFERENSIASI TERHADAP KEPUTUSAN PEMBELIAN PADA MR.DIY DI PANGKAL PINANG - Asih, Hasti Dewi; Sarmawati, Sarmawati; Wati, Mulia; Noviyanti, Indah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
This study aims to determine the extent of the influence of product differentiation strategies on consumer purchasing decisions at MR.DIY. Product differentiation is one of the marketing strategies used by companies to create added value in their products so that they appear more attractive than competing products. This study uses a quantitative approach with a survey method through the distribution of questionnaires to consumers who have shopped at MR.DIY. The analysis results indicate that product differentiation has a positive and significant influence on purchasing decisions. This means that the more diverse and unique the products offered, the higher the likelihood of consumers purchasing those products. These findings confirm that differentiation strategies are one of the important factors in increasing the appeal and purchasing decisions of consumers in the retail industry.Keywords: Product Differentiation Strategy, Purchase Decision, MR.DIY, Marketing, Consumers.